Impact of smoking and smoking cessation on overweight and obesity: Scotland-wide, cross-sectional study on 40,036 participants - Mackay, Daniel F (BioMed Central, 2013)
BACKGROUND: Weight control is cited by some people, especially adolescent girls, as a reason for commencing smoking or not quitting. The aim of this study was to explore the relationship between smoking behaviour and being overweight or obese, overall and by age and sex sub-groups. METHODS: We used data from the six Scottish Health Surveys conducted to date (1995–2010) to undertake a population-based, cross-sectional study on 40,036 participants representative of the adult (≥16 years) Scottish population. Height and weight were measured by a trained interviewer, not self-reported. RESULTS: 24,459 (63.3%) participants were overweight (BMI ≥25 kg/m(2)) and 9,818 (25.4%) were obese (BMI ≥30 kg/m(2)). Overall, current smokers were less likely to be overweight than never smokers. However, those who had smoked for more than 20 years (adjusted OR 1.54, 95% CI 1.41-1.69, p < 0.001) and ex-smokers (adjusted OR 1.18, 95% CI 1.11-1.25, p < 0.001) were more likely to be overweight. There were significant interactions with age. Participants 16–24 years of age, were no more likely to be overweight if they were current (adjusted OR 1.01, 95% CI 0.84-1.20, p = 0.944) or ex (adjusted OR 0.88, 95% CI 0.67-1.14, p = 0.319) smokers. The same patterns pertained to obesity. CONCLUSIONS: Whilst active smoking may be associated with reduced risk of being overweight among some older adults, there was no evidence to support the belief among young people that smoking protects them from weight gain. Making this point in educational campaigns targeted at young people may help to discourage them from starting to smoke.